The relationship of stress level and periodontal tissue health in soldiers from Kodam Jaya: a cross-sectional study - Setyawati, Baby Prabowo; Dita, Nadila; Herianto, Ishiko; Setiawatie, Ernie Maduratna (Frontiers in Oral Health, 2025)
BackgroundStress plays a crucial role in the development of periodontal diseases, along with other behavioral factors. Professions with high-stress levels, like the Indonesian National Army, face challenges due to demanding requirements on skills, physical endurance, and mental strength. This study aims to explore the oral and periodontal health of soldiers, with a focus on the relationship between stress levels and periodontal conditions in soldiers from Kodam Jaya.MethodsThe research method is observational with a cross-sectional approach involving 48 male respondents selected using a purposive sampling technique. All participants completed ten closed-ended questionnaires about emotions and thoughts over the past month, along with the Perceived Stress Scale (PSS). Data processing was analyzed using univariate and bivariate methods, including Spearman's correlation.ResultsThe analysis of stress levels among soldiers shows that the light category includes 11 individuals (22.9%), the moderate category consists of 29 individuals (60.4%), and the heavy category includes 8 individuals (16.7%). Therefore, out of the total 48 responses, the moderate stress level is the most common among soldiers. In terms of the distribution of BoP examinations, 7 cases (14.6%) met the healthy criteria, 2 cases (4.2%) met the mild criteria, 5 cases (10.4%) met the moderate criteria, and 34 cases (70.8%) met the severe criteria. The correlation between stress level and periodontal tissue health at BoP examination shows a moderate relationship with an r-value of 0.407 and a p-value of 0.004, indicating a significant relationship.ConclusionThere is a notable link between stress and periodontal tissue health, along with the Bleeding on Probing (BoP) assessment, in soldiers from Kodam Jaya.